Option 15 vs. A Comprehensive Financial Reporting Method for Convertible Debt. - Curry, Dudley W. (The Accounting Review, 1971)
The article compares Opinion 15 with a financial reporting method for convertible debt. Corporate capital structures often include such securities as convertible debentures, convertible preferred stocks, and stock warrants. In many cases, these instruments possess a dramatic potential for suddenly creating a huge in crease in the number of outstanding common shares and a severe dilution in earnings per share (EPS). In 1969 the Accounting Principles Board of the AICPA issued its lengthy Opinion 15, which utilized the common stock equivalent concept in prescribing when and how the dilutive effects on EPS in such cases should be shown on the face of the income statement. In order to illustrate some of the implications of this controversial Opinion and to offer a solution to the complex problems of satisfactorily reporting convertible securities in the financial statements of issuers, this article focuses on convertible debentures (CVDs). CVDs are unsecured bonds that may be exchanged for common stock of the issuer at the option of the holder at a certain ratio and during a specified period.